Education and corporate social responsibility international perspectives - Ahmad, Jamilah; Crowther, David (Emerald, 2013)
Corporate social responsibility is becoming rapidly embedded into the strategic planning and operational processes of all organizations, while at the same time our understanding of what is meant by this phenomenon continues to develop and to be extended beyond the domain of the corporate into that of all other organizations. Academics have responded to this by embedding CSR into the curricula of their respective institutions. Practice, however, differs throughout the world and this book is designed to explore these different practices in order to develop suggestions about what might be best practice and to consider the respective benefits of develop the curriculum in this manner.
Includes index.
Keywords: Social responsibility of business.; elektronické knihy; electronic books